DDEL-13. FOCUSED ULTRASOUND MEDIATED BLOOD BRAIN BARRIER DISRUPTION IN A MURINE MODEL OF PONTINE GLIOMA: A SAFETY AND FEASIBILITY STUDY. (4th December 2020) - Englander, Zachary; Wei, Hong-Jian; Pouliopoulos, Antonios; Upadhyayula, Pavan; Jan, Chia-Ing; Spinazzi, Eleonora; Canoll, Peter; Bruce, Jeffrey; Feldstein, Neil; Zacharoulis, Stergios; Konofagou, Elisa; Wu, Cheng-Chia
Abstract: BACKGROUND: Drug delivery remains a major obstacle in DIPG, as the blood brain barrier (BBB) limits the penetration of systemic therapies to the brainstem. Focused ultrasound (FUS) is an exciting new technology that, when combined with microbubbles, can open the BBB permitting the entry of drugs across the cerebrovasculature. Given that the utility of FUS in brainstem tumors remains unknown, the purpose of our study was to determine the safety and feasibility of this technique in a murine pontine glioma model. METHODS: A syngeneic orthotopic model was established by stereotactic injection of PDGF-B + PTEN -/- p53 -/- murine glioma cells (10, 000/1ul) into the pons of B6 albino mice. A single-element, spherical-segment FUS transducer (center frequency=1.5MHz) driven by a function generator through a power amplifier (acoustic pressure=0.7MPa) was used with concurrent intravenous microbubble injection (FUS+MB) to sonicate the tumor on post-injection day 14. BBB opening was confirmed with gadolinium-enhanced MRI and Evans blue. Kondziela inverted screen (KIS) testing was completed to measure motor function. Mice were either immediately sacrificed for histopathological assessment or serially monitored for survival. RESULTS: In mice treated with FUS (n=11), there was no measured deficit in KIS testing. Additionally, the degree of intra-tumoral hemorrhage and inflammation on H&E in control (n=5) and treated mice (n=5) was similar. Lastly, there was no difference in survival between the groups (control, n=6, median=26 days; FUS, n=6, median=25 days, p>0.05). CONCLUSION: FUS+MB is a safe and feasible technique to open the BBB in a preclinical pontine glioma model.